Factores que influyen en la adherencia terapéutica en hipertensión arterial en el Centro de Salud N 2. Loja - Vega Orellana, Verónica Alejandra (2019)
Arterial hypertension represents the highest risk of cardiovascular mortality, which is why adherence to treatment is vital to prevent possible complications. This investigation aimed to determine the adherence and non-adherence of patients with arterial hypertension through the Morisky test. Green by gender and age group; identify the factors that intervene in non-therapeutic adherence according to the Bonilla and De Reales test; determine the degree of risk of non-adherence to therapy and establish the degree of arterial hypertension according to the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) by gender. The study was descriptive cross-sectional prospective, with 130 hypertensive patients attended at the Health Center N 2 "Hugo Guillermo González" to whom the tests were applied to assess adherence, factors and degree of risk. The results obtained showed 18% (n = 23) of the age group of women aged 40-65 years complies with antihypertensive treatment. 19% (n = 15) of males over 65 have non-adherence to treatment. Among the socioeconomic factors, Medication Costing represents 57% (n = 74) for non-therapeutic adherence, 64% (n = 83) presented low risk to non-therapeutic adherence and 12% (n = 15) of males presented high normal blood pressure and 20% (n = 26) of normal grade women. Concluding that women have more factors to non-adherence, the main one being socioeconomic. Keywords: arterial hypertension, therapeutic adherence, non-adherence factors